Sustainability Status of Four-Finger Threadfin (Eleutheronema tetradactylum) Management in Sinaboi Sub-District Rokan Hilir District, Riau Province - Gea, Efvin Krisdayanti; Warningsih, Trisla; Arief, Hazmi (Faculty of Fisheries and Marine, Universitas Riau, 2023)
This research was conducted in July 2022 in Sinaboi District, Rokan Hilir Regency. This study aimed to analyze the sustainability status and attributes strongly influencing the sustainable management of four-finger threadfin (Eleutheronema tetradactylum) in Sinaboi District, Rokan Hilir Regency. The method used in this research is the survey method. Data sources were collected from primary data and secondary data. The purposive sampling technique selected nine respondents who met specific criteria. The data obtained were analyzed with RAPFISH to explain the ecological, economic, social, technological, and institutional dimensions that include sustainability attributes through several analyses, including Multidimensional Scaling (MDS) and sensitivity analysis (leverage analysis). The results of the Multidimensional Scaling (MDS) analysis showed that the sustainability index in the ecological dimension with a value of 61.71 and the economic size with a value of 52.12, which has a reasonably sustainable status, as well as in the social dimension with a value of 50.94, the technological extent with a value of 48.81 and the institutional size with a value of 50.40 has a less sustainable status. 9 leverage attributes are sensitive and affect the value of sustainability in the results of sensitivity analysis (leverage analysis) for each dimension. Influential details need to be considered to increase the sustainability value of four-finger threadfin in Sinaboi District